Classification and indexing practice - Bakewell, K. G. B. (London : C. Bingley ; Hamden, Conn. : Linnet Books, 1978)
This book is about principles and processes behind classification and indexing practice or system in library science
Includes index.
Bibliography: p. 196.
aia 30/6/17
Loans
Keywords: Classification; Indexing; Classification -- Books; Indexing; Documents Classification; Documents Subject indexing